Pengaruh Profitabilitas, Siklus Konversi Kas, dan Belanja Modal terhadap Cash Holding pada Perusahaan Sektor Consumer Cyclicals yang terdaftar di Bursa Efek Indonesia (BEI) Periode 2022 - 2024 - Fine Kaligis; Sri Handayani (Jurnal Riset Akuntansi Politala, 2026)
The purpose of this study is to analyze and provide evidence of the effect of profitability, cash conversion cycle, and capital expenditure on cash holding in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. This quantitative research was conducted with a causal explanatory descriptive approach, aiming to determine cause-and-effect relationships between two or more variables. The research sample consisted of 43 companies selected using a purposive sampling technique, resulting in 129 observations. Data analysis was performed using statistical analysis software with a panel data regression model, where the Fixed Effect Model (FE) was chosen as the best estimation model based on the Chow and Hausman tests. Classical assumption tests showed that the data were normally distributed and free from autocorrelation and multicollinearity. However, heteroskedasticity was detected and addressed using the robust test. Data processing states that partially, profitability and capital expenditure were proven to not significantly affect cash holding. Meanwhile, the cash conversion cycle had a negative and significant effect on cash holding.